PORTRAYING EFL STUDENTS’ LEARNING STYLES IN UTILIZING MOBILE –ASSISTED LANGUAGE LEARNING: HOW TO BE A GOOD LANGUAGE LEARNER? - Vina Fauziah Fitriani (Siliwangi University, 2020)
The advancement of new digital environments and mobile technologies has significantly led to the creation of new theories and models of language education to address the needs and opportunities of the 21st century. Mobile-Assisted Language learning (MALL) is emerged as one of the technological education in promoting ubiquitous learning among students. Since the uniqueness of individuals in processing knowledge, it is necessary to recognize the effectiveness of MALL usage in facilitating diversity of students’ learning preferences. Grounded in VARK framework of learning styles questionnaires and technological acceptance model (TAM), this study aimed to portray EFL students’ learning styles in using MALL to promote learning autonomy as well as the effectiveness of MALL as a platform to learn English. Semi-structured interview of selected participants was conducted in order to gain the data needed afterward. In analysing the data, descriptive statistics and content analysis were employed. This study found that most of the students perceived MALL as beneficial to enrich their learning styles and make them easier in learning language. Furthermore, to be a good language learner, orchestrating learning styles as well as applying metacognitive strategy in utilizing MALL is suggested. However, in integrating mobile devices in the classroom, the teacher should aware with students who are unfamiliar with autonomous learning practice, dependence and less-motivated. Thus, future research is expected to investigate teacher’s strategy in integrating MALL to promote language learning autonomy. Keywords: Language learning styles, MALL, EFL, good language learner, tertiary education